Early evolution of nutritional status and body composition after kidney transplantation - El Haggan, Wael; Vendrely, Benoît; Chauveau, Philippe; Barthe, Nicole; Castaing, Françoise; Berger, Franck; de Précigout, Valérie; Potaux, Luc; Aparicio, Michel (American journal of kidney diseases, 2002)
Previous series have dealt with nutritional status after kidney transplantation. However, few studies have described the outcome of body composition after kidney transplantation. A total of 44 cadaver kidney transplant recipients (28 men and 16 women) were followed prospectively during the first post-transplant year. Biochemical nutritional markers, dietary records, anthropometric measurements, and body composition were assessed at kidney transplantation and 3, 6, and 12 months later. By the end of the first year, serum albumin level was not significantly different from initial values. Prealbumin and retinol binding protein decreased from 42.3 +/- 10.2 mg/dL to 30.4 +/- 6.3 mg/dL and from 1.96 +/- 0.61 g/dL to 0.65 +/- 0.2 g/dL (P < 0.0001). Separating patients by gender showed that dietary caloric and protein intake increased in women only. At the end of the follow-up period, mean weight change was +5.4 kg in women (P = 0.009) and -0.9 kg in men (not significant). Body composition analyses showed that in women total fat and lean masses increased (+2.1 kg, P = 0.05, and +2.4 kg, P = 0.006), whereas in men total fat mass decreased (-1.4 kg, P = 0.04), and total lean mass tended to increase (+0.5 kg, not significant). Percentage change in total bone mass was +1.4% in women (not significant) and -2.1% in men (P = 0.05). In multivariate analyses, an independent impact of female gender on weight gain was observed, although increased fat mass was related only to energy intake. Increased total lean mass was related to low steroid doses and the absence of acute rejection and delayed graft function. Bone loss was related to male gender and high steroid doses. Changes in body composition during the first year after kidney transplantation are modulated by gender, energy intake, steroid doses, the occurrence of acute rejection, and delayed graft function.